Some features of flow and particle transport in porous structures - Aydin, M (2012)
There has been a growing interest in the study of porous and complex flow structures due to its impact in technology. This concerns not only environmental but also diagnostic and therapeutic exposure in medical research. Physics of flow within porous structures is especially important to model transport and deposition of viruses, pollutants and drugs deep in these structures. In this work we analyze numerically low and medium Reynolds number flows in axisymmetric cylindrical duct surrounded by a torus. We also consider three different particle sizes (0.02, 0.1 and 20 micron) for possible physiological and environmental applications.